Optimalisasi Aset Daerah pada Provinsi Aceh (Studi pada SKPA Provinsi Aceh) - Faridah Faridah; Muhammad zainal Abidin; Fadli Syahputra (Center for Research and Community Service (LPPM) University of Abulyatama, 2020)
This study aims to determine the relationship between regulatory understanding, asset management, asset knowledge, internal control standards (SPI) and apparatus behavior on the optimization of regional assets in the Aceh Province SKPA. The population in this study were SKPK/ SKPA with 4 fields/sub-fields and 2 employees in the asset sector. The analysis method used is qualitative and the results of the research show that understanding of regulations, asset management, asset knowledge, internal control standards (SPI) and apparatus behavior has a positive impact on the optimization of regional assets of the Aceh Government.